2013
DOI: 10.1111/jvh.12128
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the peginterferon‐α 2a and ribavirin plasma levels on viral kinetics and sustained virological response in genotype 1 HCV/HIV‐co‐infected patients with the unfavourable non‐CC IL28B genotypes

Abstract: Studies on the association between the peginterferon-α and ribavirin levels and sustained virological response (SVR) have shown yielded conflicting results, but most of them were performed before the influence of IL28B polymorphisms was known. Our aim was to assess the effects of peginterferon-α 2a and ribavirin plasma levels on viral kinetics and SVR in hepatitis C virus genotype 1 HCV-1/HIV-co-infected patients according to IL28B genotype. This was a cohort study of HCV-1/HIV-co-infected patients who were HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…We showed that at week 8 of treatment, ribavirin reached steady‐state, which fits the long elimination half‐life of 300 h . The steady‐state ribavirin plasma concentrations found in this study were in the same range as previously published in HIV/HCV co‐infected patients . However, these plasma concentrations remained lower than reported ribavirin plasma concentrations in mono‐infected patients .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We showed that at week 8 of treatment, ribavirin reached steady‐state, which fits the long elimination half‐life of 300 h . The steady‐state ribavirin plasma concentrations found in this study were in the same range as previously published in HIV/HCV co‐infected patients . However, these plasma concentrations remained lower than reported ribavirin plasma concentrations in mono‐infected patients .…”
Section: Discussionsupporting
confidence: 85%
“…This could be driven by the increasing number of patients of which ribavirin plasma concentrations were available towards weekend 48. The relation between ribavirin plasma concentrations and SVR remains controversial, as both negative and positive results have been published about this topic . These inconsistent results might be caused by, for example, differences in treatment, heterogeneity of populations, variation in analytical assays and small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Dropout data were included up to the last available visit for individuals on treatment. The Rbv levels before week 4 were excluded from the analysis, as we had previously observed that Rbv concentrations were significantly lower dur-ing the first 2 weeks of treatment and became stable from week 4 onward (13).…”
Section: Methodsmentioning
confidence: 99%
“…During the triple-therapy course, Rbv plasma concentrations were compared between the period when Rbv was given concomitantly with TVR (weeks 0 to 12) and the period after TVR discontinuation (week 13 forward), using analyses of repeated measures. Additionally, the Rbv levels during TT were compared with both those observed in the same subjects during a previous DT course and those for a cohort of 125 adult Caucasian HCV-1/HIV-coinfected patients treated with pegIFN-␣ plus Rbv, without Rbv dose reduction during the DT course, which were measured by reverse-phase high-performance liquid chromatography in the same hospital (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation